Plant-soil-enzyme C-N-P stoichiometry and microbial nutrient limitation responses to plant-soil feedbacks during community succession: A 3-year pot experiment in China - Xu, Hongwei; Qu, Qing; Wang, Zhanhui; Xue, Sha; Xu, Zhenfeng (Frontiers in Plant Science, 2022)
Studying plant-soil feedback (PSF) can improve the understanding of the plant community composition and structure; however, changes in plant-soil-enzyme stoichiometry in response to PSF are unclear. The present study aimed to analyze the changes in plant-soil-enzyme stoichiometry and microbial nutrient limitation to PSF, and identify the roles of nutrient limitation in PSF. Setaria viridis, Stipa bungeana, and Bothriochloa ischaemum were selected as representative grass species in early-, mid-, and late-succession; furthermore, three soil types were collected from grass species communities in early-, mid-, and late-succession to treat the three successional species. A three-year (represents three growth periods) PSF experiment was performed with the three grasses in the soil in the three succession stages. We analyzed plant biomass and plant-soil-enzyme C-N-P stoichiometry for each plant growth period. The plant growth period mainly affected the plant C:N in the early- and late- species but showed a less pronounced effect on the soil C:N. During the three growth periods, the plants changed from N-limited to P-limited; the three successional species soils were mainly limited by N, whereas the microbes were limited by both C and N. The plant-soil-enzyme stoichiometry and plant biomass were not significantly correlated. In conclusion, during PSF, the plant growth period significantly influences the plant–soil–microbial nutrient limitations. Plant-soil-enzyme stoichiometry and microbial nutrient limitation cannot effectively explain PSF during succession on the Loess Plateau.